Handmade Painting on an Oversized T-shirt with Balinese Motif Ornaments at the Agung Bali Collection - Putra, Fachri Permana; Budiarta, I Dewa Putu Gede; Supriyatini, Sri (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
The thesis with the title Handmade painting on an oversized t-shirt with Balinese motif ornaments at the Agung Bali Collection is motivated by the start-up world which is increasingly rampant in society. The author has hopes in the future to become an artist and also have a business. By conducting research at the Agung Bali Collection, the authors gain entrepreneurial knowledge such as management science, marketing science, capital and so on. By having this entrepreneurial knowledge, the author has an idea to market his work. Because it's not enough just to make a work, you also have to know how to market and manage it. The stages in conducting this research are exploration, interviews and analysis. The author conducts exploration first, looking for research on knowledge developed by partners. After that, interviews were conducted with the aim of collecting data and research documentation. Finally, analysis is carried out by analyzing the research and documentation obtained and then adjusting it to the tastes of the market and society. An oversized painted t-shirt was formed. oversized t-shirts are chosen because they are on the rise in society. The capital obtained is approximately one million rupiah. The author also has his own branding, namely Fach handmade painting. Fach is taken from the author's name "Fachri". In the MBKM TA, the author created six works with surface designs from the Agung Bali Collection. Marketing used through the social media platform Instagram and dissemination.